A soul as cold as frost ebook - Kropf, Jennifer (The Winter Souls Series, 2022)
"Merry Christmas to all, and to all a good fright..." What if St. Nicholas was really a young, mad trickster and you had the one thing he wanted? What if the only person who agreed to protect you from him had a past of letting those he's meant to protect die? What if you were in the wrong place at the wrong time, and you gained the ability to see a whole other world tucked into the cracks of your own? Helen Bell is a student with a past she'd rather not remember and a high school social life that doesn't exist. Almost everyone she passes either forgets she's there or doesn't notice her in the first place. She survives her life in the shadows by focusing on her studies. Until the day everything changes. When a strange encounter leaves Helen able to see a species of invisible people existing among us, naturally she assumes she's going delusional or is getting ill from the cold Canadian weather. But when a young, handsome Winter guardian appears to aid her in a crisis, and a train horn starts blasting over the city in a search to hunt her down, she finds herself in the middle of a war where nothing is quite as it seems, and what's "right" isn't always right. "No matter what happens," her Winter guardian warns as creatures all down the street begin to shriek and freeze in place, "Don't move a muscle..." Zane Cohen is a young, retired Patrolman. Even though he craves mischief and would rather play tricks on snow rabbits than get dragged back into the guardian life, he finds he can't help himself when he meets Helen Bell. She's not suitable to play the games of the Rime Folk. If she's not careful, she's going to get herself killed. And he shouldn't care, but... But a long time ago, he believed in an ancient "Truth". This same Truth begins calling Helen's name across the snow, forcing her to make the ultimate decision to either run back to her empty life, or do the unthinkable—to face off with the Snow Queen in The Quarrel of Sword and Bone; a match that takes place in a Winter arena before one thousand witnesses and will likely mean certain death. So, the retired Patrolman becomes not so retired after all. A Soul as Cold as Frost is Jennifer Kropf's debut novel, ideal for fans of The Lion, the Witch, and the Wardrobe by C.S. Lewis, and The Nutcracker and the Four Realms by Meredith Rusu and Ashleigh Powell. Book Facts: *The Winter Souls Series is an adventure for ages 10+, loved by teens and parents alike. *This series contains a Christian allegory. *A Soul as Cold as Frost was rewritten, reimagined, and reformatted with illustrations by Kyannah Durocher in 2024 for a better reading experience. "Wow, I loved this book! This book was a magical twist between Narnia, Alice in Wonderland, and Spirited Away, yet somehow read as effortlessly original. It was gripping, fast paced and full of action, yet not lacking in heart. Highly recommended for young YA readers upwards." – Alice Ivinya, USA Today Bestselling author of Stars May Burn "The Chronicles of Narnia meets Harry Potter. This fantastic winter tale is the perfect blend of classic portal fantasy and the magical world co-existing with our own. This magical Christian fantasy adventure totally hits the spot and got everything right. It is a beautiful reminder of what is truly important in life." - USA Today Bestselling author Astrid V. J.